Verification of regulatory activity reports in the heating sector: process and outcomes - Morkūnaitė, Deimantė; Raziūnienė, Daiva (Buhalterinės apskaitos teorija ir praktika, 2021)
The reports of the heating sector are one of the most important sources of heating data, accurate and reasonable pricing and is an essential objective of public interest. The verification of the reports on regulated activities is particularly important to regulate interpretation of the principles of companies’ operating cost and accounting separation systems. The purpose of the article is to identify the main elements of the regulatory activities report whereas have to be improved and needs more attention of auditors and regulators. There were examined 52 reports of Lithuanian heating sector companies using document (content) analysis approach. Misstatements were analysed using specific evaluation criteria to identify areas for improvement. The development of an appropriate methodology and the efficient functioning of the process should help to avoid errors or inaccuracies in determining, fair recognition, disclosure and valuation of fixed assets as an essential factor of heating prices.